2022
DOI: 10.30699/jambs.30.139.123
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, Stress, and Resiliency in Iranian Families with Autistic Children

Abstract: 10.30699/jambs.30. 139.123 Background & Objective: Caring for children with autism is associated with parental stress and puts them at risk for depression and anxiety. Increasing resilience may help reduce the parents' stress. The main objective of this study was to investigate the relationship between resilience and anxiety, depression, and stress in families with autistic children in 2018. Materials & Methods:In this cross-sectional study, 137 members of the target families were selected randomly. The case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Moreover, families often witnessed changes in family roles, routines, co-parenting dynamics (e.g., disturbed marital, sibling, and family relationships), and alterations in community and work settings (Adams et al, 2020;Glinski & Valjee, 2019;Matenge, 2013;Schlebusch & Dada, 2018). Other global studies, including those from Africa, indicated these challenges affecting women more than men resulting in maternal stress and mental instability when caring for their ASD children (Asmare et al, 2023;Benrween et al, 2022;Di Renzo et al, 2022;Hosseini et al, 2022;Li et al, 2022). The financial strain in caring for the child with ASD has been widely reported in the WHO Afro-region (Allotey, 2020;Mbamba & Ndemole, 2021;Mthombeni & Nwoye, 2018;Oti-Boadi, Oppong Asante, et al, 2020;Van der Merwe, 2015;Van Rooyen, 2016).…”
Section: Challenges Experienced By Familiesmentioning
confidence: 99%
“…Moreover, families often witnessed changes in family roles, routines, co-parenting dynamics (e.g., disturbed marital, sibling, and family relationships), and alterations in community and work settings (Adams et al, 2020;Glinski & Valjee, 2019;Matenge, 2013;Schlebusch & Dada, 2018). Other global studies, including those from Africa, indicated these challenges affecting women more than men resulting in maternal stress and mental instability when caring for their ASD children (Asmare et al, 2023;Benrween et al, 2022;Di Renzo et al, 2022;Hosseini et al, 2022;Li et al, 2022). The financial strain in caring for the child with ASD has been widely reported in the WHO Afro-region (Allotey, 2020;Mbamba & Ndemole, 2021;Mthombeni & Nwoye, 2018;Oti-Boadi, Oppong Asante, et al, 2020;Van der Merwe, 2015;Van Rooyen, 2016).…”
Section: Challenges Experienced By Familiesmentioning
confidence: 99%